Evidence for the presence of a human saprophytic oral bacterium, Mycoplasma faucium, in the skin lesions of a psoriatic patient. (27th December 2021) - Arabatzis, Michael; Velegraki, Aristea
Abstract: Psoriasis is currently regarded a mixed autoimmune and autoinflammatory disease. This report describes for the first time the detection of a saprophytic, human oral Tenericutes species, Mycoplasma faucium, in the skin lesions of a patient presenting initially guttate and later plaque psoriasis. An unusual finding in standard histopathology investigation consisted of round and oval thinly stained or unstained, possibly intracellular structures, apparently directly pressing on keratinocyte nuclei of the psoriatic stratum spinosum. In ultrastructural study, wall‐less bacteria were present intracellularly in the keratinocytes, mainly of the psoriatic stratum spinosum, and extracellularly in the upper dermis of the psoriatic lesions. M . faucium was consistently detected and identified in the psoriatic skin by general Tenericutes polymerase chain reaction and sequencing in two biopsies performed 31 months apart. This case raises new questions concerning the pathogenesis of psoriasis and its accepted autoimmune/autoinflammatory nature.